IL-4 and IL-13 Differentially Regulate TLR-Induced Eosinophil-Basophil Differentiation of Cord Blood CD34+ Progenitor Cells - Reece, Pia (Public Library of Science, 2014)
Intrauterine environmental exposures have been shown to influence neonatal immunity and subsequent allergic disease development. We have previously shown that fewer lipopolysaccharide (LPS)-stimulated eosinophil-basophil (Eo/B) colonies grow from cord blood (CB) of high-atopic risk infants, compared to low-atopic risk infants. In the present study, we investigated whether a surrogate ex vivo TH2 milieu (i.e., either IL-4 or IL-13) could represent an underlying mechanism to explain our previous findings. CB CD34+ cells from healthy donors were cultured with IL-4 or IL-13 (in combination with LPS) and assessed for Eo/B differentiation using methylcellulose cultures and flow cytometry for related intracellular signalling pathways. Pharmacological inhibitors were added to the methylcellulose cultures to determine the effect of blocking intracellular signalling in CB CD34+ cells in relation to Eo/B colony forming unit (CFU) formation. Stimulation of CD34+ cells with IL-4, but not IL-13, reduced Eo/B CFU formation in the presence of LPS; this was found to be dependent on IL-4Rα and not IL-13Rα1. Additionally, IL-4 reduced the expression of ERK 1/2 after LPS stimulation, which was recovered by inhibition of IL-4Rα. While IL-13 did not have an inhibitory effect on ERK 1/2 expression, inhibition of ERK 1/2 significantly reduced Eo/B CFU formation. Thus, the responsiveness of CB CD34+ progenitor cells to LPS is differentially regulated by the TH2 cytokines, IL-4 and IL-13. This may have implications for in utero interactions between placental-derived pro-allergic cytokines and neonatal progenitor cells influencing Eo/B-mediated inflammatory responses in early life.